DESAIN DASHBOARD INTERAKTIF KINERJA KEUANGAN GUNA MENDUKUNG KEPUTUSAN BISNIS LEVEL TOP MANAJEMEN PADA CV BIMA TECHNOLOGIES - Mufiro, Adelia; Winarno, Wahyu Agus; Wardhaningrum, Oktaviani Ari (ABDI MAKARTI, 2025)
As a rapidly growing technology company, CV Bima Technologies faces the challenge of making quick and effective business decisions. A key issue is the lack of detailed visualized financial information, such as receivables per customer and debts per creditor. This community service project aims to design a decision support system using interactive dashboards powered by Microsoft Power BI to provide real-time insights into business development and monitor ongoing projects. The method involves collecting primary data through interviews and additional financial data, which are then analyzed and simplified for visualization. The resulting interactive dashboard displays detailed customer receivables, including project name, customer name, nominal amount, repayment date, receivable status, outstanding debt, and percentage of collectable receivables. Debt visualization includes item name, debt amount, creditor, due date, debt status, and debt status amounts. Additionally, the project realization report provides a list of projects, goods and services used, planned prices, bid prices, and actual expenditures. The implementation of this system allows CV Bima Technologies’ management to monitor financial health and project progress in real time, enabling more informed decision-making and improved business control.